Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 78650 by Pratah last updated on 19/Jan/20

Commented by mr W last updated on 19/Jan/20

=x^2 +1

=x2+1

Commented by john santu last updated on 20/Jan/20

sorry sir, yesterday already   slept

sorrysir,yesterdayalreadyslept

Commented by Pratah last updated on 19/Jan/20

sir john santu

sirjohnsantu

Commented by Pratah last updated on 19/Jan/20

please

please

Answered by mind is power last updated on 19/Jan/20

p=3x^4 +2x^3 +x^2 +2x−2=3x^4 −3+2x^3 +2x+x^2 +1=3(x^2 −1)(x^2 +1)  +2x(1+x^2 )+x^2 +1=(x^2 +1)(3(x^2 −1)+2x+1)=(x^2 +1)(3x^2 +2x−2)  Q=x^5 +x^4 −x^3 −2x−1=x^5 +x^3 +x^4 −1−2x−2x^3   =x^3 (1+x^2 )+(x^2 −1)(x^2 +1)−2x(1+x^2 )=(1+x^2 )(x^3 +x^2 −1−2x)  =(1+x^2 )(x^3 +x^2 −2x−1)  So (1+x^2 )∣gcd(p,q)  x^3 +x^2 −2x−1 and 3x^2 +2x−2   has dufferent roots⇒ primes  ⇒  gcd=1+x^2

p=3x4+2x3+x2+2x2=3x43+2x3+2x+x2+1=3(x21)(x2+1)+2x(1+x2)+x2+1=(x2+1)(3(x21)+2x+1)=(x2+1)(3x2+2x2)Q=x5+x4x32x1=x5+x3+x412x2x3=x3(1+x2)+(x21)(x2+1)2x(1+x2)=(1+x2)(x3+x212x)=(1+x2)(x3+x22x1)So(1+x2)gcd(p,q)x3+x22x1and3x2+2x2hasdufferentrootsprimesgcd=1+x2

Commented by Pratah last updated on 19/Jan/20

thanks

thanks

Answered by Rasheed.Sindhi last updated on 19/Jan/20

gcd(x^5 +x^4 −x^3 −2x−1,3x^4 +2x^3 +x^2 +2x−2)  =gcd(3(x^5 +x^4 −x^3 −2x−1),3x^4 +2x^3 +x^2 +2x−2)   determinant ((,(x+1)),((3x^4 +2x^3 +x^2 +2x−2)),(+3x^5 +3x^4 −3x^3 +0x^2 −6x−3)),(,(+_− 3x^5 +_(−) 2x^4 +_(−)    x^3 +_(−) 2x^2 −_(+) 2x)),(,(3(x^4 −4x^3 −2x^2 −4x−3))),(,(=3x^4 −12x^3 −6x^2 −12x−9)),(,(+_− 3x^4 +_(−)    2x^3 +_(−)     x^2 +_(−)    2x−_(+) 2)),(,(−14x^3 −7x^2 −14x−7)),(,(=−7(2x^3 +x^2 +2x+1))))     determinant ((,(x+1)),((6x^3 +3x^2 +6x+3)),(+6x^4 +4x^3 +2x^2 +4x−4)),(,(+_− 6x^4 +_(−) 3x^3 +_(−) 6x^2 +_(−) 3x)),(,(x^3 −4x^2 +x−4)),(,(6(x^3 −4x^2 +x−4))),(,(=6x^3 −24x^2 +6x−24)),(,(+_− 6x^3 +_(−) 3x^2 +_(−) 6x+_(−) 3)),(,(−27x^2 −27)),(,(=−27(x^2 +1))))     determinant ((,(6x+3)),((x^2 +1)),(    6x^3 +3x^2 +6x+3)),(,(+_− 6x^3            +_(−) 6x)),(,(    3x^2 +3)),(,(+_− 3x^2 +_(−) 3)),(,0))  gcd=x^2 +1

gcd(x5+x4x32x1,3x4+2x3+x2+2x2)=gcd(3(x5+x4x32x1),3x4+2x3+x2+2x2)|x+13x4+2x3+x2+2x2)+3x5+3x43x3+0x26x3+3x5+2x4+x3+2x2+2x3(x44x32x24x3)=3x412x36x212x9+3x4+2x3+x2+2x+214x37x214x7=7(2x3+x2+2x+1)||x+16x3+3x2+6x+3)+6x4+4x3+2x2+4x4+6x4+3x3+6x2+3xx34x2+x46(x34x2+x4)=6x324x2+6x24+6x3+3x2+6x+327x227=27(x2+1)||6x+3x2+1)6x3+3x2+6x+3+6x3+6x3x2+3+3x2+30|gcd=x2+1

Commented by Pratah last updated on 19/Jan/20

great

great

Terms of Service

Privacy Policy

Contact: info@tinkutara.com